Prevention program of groin pain in athlete - Aoto, K.; Hirano, A.; Uemura, K.; Misonoo, G.; Oda, K.; Miyakawa, S. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Although groin pain is common in the athlete, it is often difficult, expensive and time consuming to treat, and thus, preventive strategies and activities are important. There are very few studies examining prevention for groin pain in sport. We would like to introduce the prevention program of groin pain that we are doing. Methods The prevention program consisted of several exercises including strengthening, coordination, and core stability exercises for the muscles related to the pelvis. Results & Discussion The improvement of the dynamic alignment was seen after the exercises. The development of groin pain tended to decrease. Conclusion To further verify the effect of the prevention program, it is necessary to perform a cluster-randomized trial.